The Influence of Project Based Learning on Learning Outcomes, Creativity and Student Motivation in Science Learning at Elementary Schools - Pangestu, Kinanti; Malagola, Yopi; Robbaniyah, Inayatur; Rahajeng, Dyah (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2024)
Project-Based Learning (PBL) is a pedagogical approach that centers on students actively engaging in real-world, meaningful projects to explore and construct knowledge. This study investigates the influence of PBL on learning outcomes, creativity, and student motivation in science learning at the elementary school level. In addition, this study aims to explore how PBL, as an instructional approach, affects learning outcomes, creativity and student motivation in science education. The research employed a quantitative approach through a quasi-experimental method. The sample consisted of elementary school students in Surabaya, Indonesia, who were exposed to PBL activities in their science classes, while a control group experienced conventional instruction. Both groups completed pre- and post-tests to assess changes in creativity and motivation. The research design employed was a true experimental design, involving the formation of two groups, namely the control and experimental groups, through random sampling. This study's results indicate that PBL significantly impacts student learning outcomes, motivation, and creativity in science education. These findings contribute to the existing literature on PBL and its influence on learning outcomes, creativity, and student motivation in science learning. The results underscore the importance of integrating PBL as a practical instructional approach in elementary school classrooms to foster creativity and enhance student motivation. Educators and policymakers can use these insights to promote innovative teaching methods that encourage active participation, critical thinking, and creative problem-solving skills in science education at the elementary level.